Sosialisasi Kegagalan Implementasi Kebijakan Plastik Sekali Pakai Dimasa Covid -19 Dan Langkah Antisipatif Mendukung Teknologi Hijau - Flora Elvistia Firdaus; Rinette Visca (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Plastic is a political agenda that always ranks at the top in several countries. Several efforts have been made, starting from studies, providing education, and to producers and consumers to save the environment. The COVID-19 pandemic has disrupted plastic reduction policies covering personal protective equipment (PPE), plastic bags, etc. from regional to national levels, which resulted in significant changes in managing plastic wastes and the negative impacts on the environment and human health. This paper explores the readjustment of policies during the COVID-19 pandemic and its potential implications to the environment. The sudden increase in plastic waste due to the COVID-19 pandemic indicates the importance of strengthening plastic reduction policies, thereby making room for technological innovation to achieve a green economy and provide policy recommendations for future research directions.